(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The NACA 0015 airfoil model underwent wind tunnel testing using the Educational Wind Tunnel-PC Linked Three Component Balance (WT300). The primary objective of the experiment was to assess the airfoil’s aerodynamic characteristics at constant velocities of 20m/s and 30m/s across Angles of Attack (AOA) with a vast variety, ranging from 0 degrees to 35 degrees AOA. The wind tunnel’s three-component balance directly measured the drag and lift forces. Analysis of the data revealed Cl (coefficient of lift) and Cd (coefficient of drag) values of approximately -0.7 and 0.9, respectively. Comparing the two speeds, the lift-to-drag ratio was higher at 20m/s compared to 30m/s. Additionally, the coefficient of lift at 20m/s was greater than that at 30m/s. Rather than using smoke visualization, the tuft flow technique was employed in this experiment, which involves attaching filaments or strings at various positions on the model for flow visualization. The results indicated that stalling occurred for the NACA 0015 airfoil at an AOA range between 20° < α ≤ 30° when the speed was set at 30m/s, while at 20m/s, stalling occurred at 15° within the AOA range of 10° < α < 20°.